A linear synthesis of gemcitabine. (10th April 2015) - Brown, Kylie; Weymouth-Wilson, Alex; Linclau, Bruno
Abstract: Gemcitabine, 2′-deoxy-2′, 2′-difluorocytidine, is currently prescribed against a number of cancers. Here we report a linear synthesis of gemcitabine with a high-yielding direct conversion of 3, 5-di- O -benzoyl-2-deoxy-2, 2-difluororibose into the corresponding glycosyl urea as the key step, followed by conventional conversion to the cytosine base via the uracil derivative. The process proceeded with modest anomeric selectivity. Graphical abstract: Highlights: A linear synthesis of gemcitabine has been achieved. The key step is a urea introduction to an unactivated 2, 2-difluorinated furanose. Only moderate anomeric selectivity was obtained.